Arabidopsis miR156 Regulates Tolerance to Recurring Environmental Stress through SPL Transcription Factors . Issue 4 (25th April 2014) - Stief, Anna; Altmann, Simone; Hoffmann, Karen; Pant, Bikram Datt; Scheible, Wolf-Rüdiger; Bäurle, Isabel
Abstract : The authors show that a well-conserved miRNA-transcription factor module implicated previously in developmental control regulates responses to repeated heat stress. They provide a conceptual framework for the integration of environmental stress responses with development to optimize growth under natural conditions. Abstract: Plants are sessile organisms that gauge stressful conditions to ensure survival and reproductive success. While plants in nature often encounter chronic or recurring stressful conditions, the strategies to cope with those are poorly understood. Here, we demonstrate the involvement of ARGONAUTE1 and the microRNA pathway in the adaptation to recurring heat stress (HS memory) at the physiological and molecular level. We show that miR156 isoforms are highly induced after HS and are functionally important for HS memory. miR156 promotes sustained expression of HS -responsive genes and is critical only after HS, demonstrating that the effects of modulating miR156 on HS memory do not reflect preexisting developmental alterations. miR156 targets SPL transcription factor genes that are master regulators of developmental transitions. SPL genes are posttranscriptionally downregulated by miR156 after HS, and this is critical for HS memory. Altogether, the miR156-SPL module mediates the response to recurring HS in Arabidopsis thaliana and thus may serve to integrate stress responses with development.